Membangun Loyalitas Pelanggan Kopi Kenangan di Era Digital : Pendekatan Pemasaran Lanjutan - Sopyan, Ismail; Zahra, Giskha Aulia; Utami N.A, Tri (UNIVERSITAS SERAMBI MEKKAH, 2025)
Transformation in the digital era has changed the landscape of marketing strategies, including building customer loyalty. This research explores the advanced marketing strategies implemented by Kopi Kenangan, one of the leading coffee brands in Indonesia, in strengthening customer loyalty amidst increasingly intense industry competition. This research highlights the role of digital technology, service personalization, and the use of social media in creating unique and engaging consumer experiences. The strategies discussed include analyzing customer data to understand consumer preferences, implementing app-based loyalty programs, and collaborating with influencers to enhance customer interaction. The research findings indicate that effective digital-based marketing can strengthen customer relationships with the brand, increase retention rates, and drive business growth. This study provides recommendations for other business operators to leverage digital technology in building customer loyalty strategically and sustainably.